Emocionalna disregulacija i trauma mladih: perpetuum mobile - Mitkovic-Voncina, Marija; Lero, Marija; Lestarevic, Sanja; Pejovic-Milovancevic, Milica (Medical Research, 2025)
Both emotion dysregulation (ED) and traumatic experiences, especially interpersonalnal trauma in childhood, are increasingly being recognized as transdiagnostic risk factors for mental disorders during developmental age as well as later in life. The aim of this review is to explore the existing data regarding the potentially bidirectional relationship between ED and trauma, focusing on the way they could maintain each other to create a “perpetuum mobile” that shapes the mental health outcomes of youth. There is relatively consistent evidence that developmental traumatic experiences, especially child maltreatment, have adverse effects on ED, through various psychological mechanisms (such as social learning, interpretation of social cues, attachment, active invalidation of their emotional experiences) as well as neurobiological mechanisms (such as structural and functional abnormalities of the emotion-regulation-related neural areas caused by aberrant stimulation, stress-response system hyperactivity, and involvement of other physiological systems). In turn, certain evidence indicate that ED may maintain and worsen trauma by impairing trauma processing and eliciting trauma-related symptoms and conditions, as well as by inducing new interpersonal traumatic exposures via factors such as shame, mental disorders and proneness to aggressive behaviors. This potential “perpetuum mobile” could be active not only in a lifetime of one person, but possibly spread through generations via different mechanisms. More research is needed to explore the nature of this complex relationship, and especially the ways ED in youth sets the ground for further maintenance of trauma. It is challenging to empirically conclude on the true direction of this relationship in different studies, implying the need for methodological rigor in future investigations. Practical implications refer to all levels of prevention when it comes to both youth exposure to trauma and ED, but also to stopping the potential “perpetuum mobile”, by preventive actions in both directions. Keywords: developmental trauma, emotion dysregulation, interplay, adolescents, youth